2017
DOI: 10.1002/smll.201700007
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Influence of Work Functions of Cathodes on Efficiencies of Perovskite Solar Cells

Abstract: Though various efforts on modification of electrodes are still undertaken to improve the efficiency of perovskite solar cells, attributing to the large scope of these methods, it is of significance to unveil the working principle systematically. Herein, inverted perovskite solar cells based on indium tin oxide (ITO)/poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS)/CH NH PbI /phenyl-C61-butyric acid methyl ester (PC BM)/buffer metal/Al are constructed. Through the choice of different buffer me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…In theory, the former requires that the WF of TCO is smaller than that of perovskite, i.e., WF TCO < WF perovskite , and the latter needs that the CBM of perovskite should be much closer to the E F of TCO. In fact, previous work has suggested that the WF of cathode has a great influence on the performance of planar device …”
Section: Introductionmentioning
confidence: 99%
“…In theory, the former requires that the WF of TCO is smaller than that of perovskite, i.e., WF TCO < WF perovskite , and the latter needs that the CBM of perovskite should be much closer to the E F of TCO. In fact, previous work has suggested that the WF of cathode has a great influence on the performance of planar device …”
Section: Introductionmentioning
confidence: 99%
“…And lastly different methods for optimizing the alignment of the energy bands of the used materials should be considered to further improve the cells performance. Promising candidates are the inclusion of buffer layer to bridge the gap between two bands, the doping of charge carrier transport layers and the perovskite itself to enhance charge carrier injection and mobility and the adjustment of the perovskites energy bands by changing its chemical composition …”
Section: Discussionmentioning
confidence: 99%
“…Organic electronic devices are becoming increasingly commercially viable due to their continuously improving efficiency in the recent years and the tremendous amount of research targeted in maintaining relatively high efficiencies along with their low cost of production and technological ease of transfer. [1,2] The recently recorded high efficiencies of these devices [3][4][5][6][7] are still well below the theoretical maximum efficiencies. [8] It is now well known that to improve the performance of these devices it is imperative to have a thorough the anode is made of organic materials (polymers, small molecules), of graphene oxide [9] or even of inorganic material like NiO.…”
Section: Introductionmentioning
confidence: 92%